APLIKASI UJI KEPRIBADIAN BERDASARKAN MULTIPLE INTELLIGENCES BERBASIS WEB MENGGUNAKAN METODE PROTOTYPING - Gina Rahmadhany; Khairul Umam Syaliman bin Lukman (Jurnal Komputer Terapan, 2021)
Multiple intelligences (MI) was developed by Howard Gardner, a developmental psychologist and professor of Harvard University, United States. His theory of Multiple Intelligences (MI) was published in 1993. Gardner believes that as his name implies, multiple intelligences, human cognitive competencies are better described in terms of multiple intelligences such as abilities, talents, or mental skills, which are called intelligences. Everyone has their own abilities and has a certain level in each of these intelligences. From this research resulted in a web-based application that can identify the type of personality and suggestions for each personality then interesting info about each personality. Built using the Laravel framework, PHP and MYSQL programming languages, and using the prototyping method in two iteration, to make the requirements of user for the system can be fulfilled. The results of usability testing through 30 respondents stated that the system was very feasible to use, then using a validation test the results obtained on the system and manual calculations obtained accurate results from the ten samples used and finally the results of the user acceptance test, it was found that all functional systems were running according to which are expected.